Multi-radio and multi-hop LoRa communication architecture for large scale IoT deployment. (September 2022) - Prade, Lucio; Moraes, Jean; de Albuquerque, Eliel; Rosário, Denis; Both, Cristiano Bonato
Abstract: Internet of Things (IoT) devices must cover large areas in the farmlands to collect vital information and avoid financial losses to improve agriculture efficiency. It is crucial to hold data acquisition in farms where network connectivity is a limitation in this context. Long-Range Wide Area Network (LoRaWAN) provides a broad coverage area tailored for IoT applications using unlicensed frequency bands with low power consumption and throughput. However, LoRaWAN might not be suitable for data acquisition on farms with hundreds of kilometers. Therefore, a multi-hop Long-Range (LoRa) network emerged as a promising solution in applications requiring extensive deployment. However, a multi-hop architecture must be designed to cope with the limitations of LoRa deployment in large-scale scenarios. This article introduces a multi-radio and multi-hop LoRa communication architecture to enhance the coverage and service for large-scale IoT deployment in rural areas, called Multi-LoRa . We present a hardware prototype for physically implementing the Multi-LoRa architecture. The results show that Multi-LoRa effectively mitigates the difficulties of multi-hop communication over LoRa for large-scale IoT deployment. Multi-LoRa reduced the delay by 60% and packet loss by 2.9% compared to different setups of Multi-LoRa on a small-scale physical testbed and large-scale simulation environment.